PERAN PEMERINTAH DAERAH DALAM PEMBANGUNAN INFRASTRUKTUR JALAN DI KOTA BATAM - Wahyuningsih, Novi; Lodan, Karol Teovani; Dompak, Timbul; Salsabila, Lubna (Jurnal Progress Administrasi Publik, 2024)
As a government that has a very strategic authority and position related to its obligations as a "public service" to improve the welfare, prosperity, security and peace of society, regional governments have a very important role in regional development planning. Regional governments in this case must carry out their main tasks which of course must be adjusted to the vision, mission, goals and objectives that will be achieved later. Development is a complex process that requires significant changes in social structures, cultural values, and institutional frameworks to promote faster economic growth, reduce income disparities, and eradicate poverty. Apart from roads, trucks, cable cars and trains, roads are all road elements protected by land transportation infrastructure, including supporting buildings and traffic instruments that are above ground and above water. This scientific work was written using descriptive techniques. This approach can be described as a critical thinking methodology that involves reading articles or other items. In accordance with Law Number 23 of 2014, autonomous regional governments led by regional heads are organized by regional governments. One of the cities or districts in the Riau Islands Province that is still developing is Batam City. Regional governments are still concerned and monitoring infrastructure development. During the Covid-19 epidemic, environmental and meteorological conditions, obstacles and the process of road infrastructure development also occurred. However, considering the existing challenges and setbacks, this can be used as a basis for review and improvement in preparing for the next phase of regional government growth. Therefore, these difficulties do not become a challenge for local governments during the development process; instead, it can be taken into account later.   Keywords: Local Government; Development; Infrastructure